Silicone-containing turpentine-based UV-curable acrylate prepolymer and preparation method and application thereof

By grafting reaction and hydrolysis of turpentine-based carboxylic acid, silicon-containing turpentine-based UV cured acrylate prepolymer was prepared, which solved the environmental protection and compatibility problems in the preparation of traditional silicone polymers, and achieved high-performance and environmentally friendly UV cured materials.

CN118724939BActive Publication Date: 2025-04-29SOUTH CHINA AGRICULTURAL UNIVERSITY +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410673913.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-28
Publication Date
2025-04-29
Estimated Expiration
2044-05-28

AI Technical Summary

Technical Problem

Traditional silicone polymers are prepared by thermal curing, which have environmental protection and energy saving problems, and are poorly compatible with other resins, which limits their application.

Method used

Turpentine carboxylic acid was grafted with glycidyl methacrylate and gamma-glycidyl etheroxypropyl trimethoxysilane to obtain TPA-GMA-KH560 graft and hydrolyzed by sol-gel method to obtain a silicon-containing turpentine-based UV cured acrylate prepolymer.

Benefits of technology

It realizes high-performance silicone materials that quickly cure at room temperature, with good mechanical properties, thermal stability and chemical resistance, while reducing the consumption of fossil energy and meeting environmental protection and energy-saving requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004863459700000021
    Figure BDA0004863459700000021
  • Figure HDA0004863459710000011
    Figure HDA0004863459710000011
  • Figure HDA0004863459710000012
    Figure HDA0004863459710000012
Patent Text Reader

Abstract

The present invention belongs to the technical field of UV curing materials, and specifically relates to a silicon-containing turpentine-based UV curing acrylate prepolymer and its preparation method and application. The present invention uses glycidyl methacrylate and γ-glycidyloxypropyltrimethoxysilane to graft turpentine-based carboxylic acid, uses carboxylic acid and epoxy ring-opening reaction, introduces double bond groups containing UV curable and hydrolyzable alkoxy groups, and obtains TPA-GMA-KH560 grafts; then the TPA-GMA-KH560 grafts are hydrolyzed by a sol-gel method to obtain a silicon-containing turpentine-based UV curing acrylate prepolymer. The present invention introduces silicone into UV curing materials, which can increase the chemical resistance of the material. The Si-O-Si bonds generated after the hydrolysis of the TPA-GMA-KH560 grafts can also give the molecular chain a certain flexibility, so that the silicone polymer has good mechanical properties and thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a silicon-containing turpentine-based UV-curable acrylate prepolymer and a preparation method and application thereof. Background Art

[0002] Ultraviolet (UV) curing is an advanced material surface treatment technology that appeared in the 1960s. It uses UV to trigger chemically active liquid materials to quickly polymerize and crosslink, and then cure into solid materials in a short time. Compared with traditional thermal curing and / or air-drying curing technologies, UV curing technology has the advantages of low energy consumption, low environmental pollution (solvent-free formula) and rapid curing at room temperature. In addition, the thickness of the cured coating remains basically unchanged, the surface properties of the film are also better, and the product quality is also higher. Therefore, UV curing technology has been widely used, especially for protecting and decorating surfaces.

[0003] Silicone polymers have many excellent physical and chemical properties, such as low-temperature elasticity, high-temperature stability, insulation, weather resistance, corrosion resistance, ozone aging resistance, radiation resistance, physiological inertness, and low surface energy properties. They are widely used in many fields such as aerospace, electronics, chemicals, construction, medical care, and daily chemicals. However, traditional silicone polymers are usually prepared by thermal curing, which does not meet the requirements of environmental protection and energy saving. In addition, the compatibility of silicone resins with other resins is also poor, which limits their application. In order to obtain high-performance silicone resins, it is necessary to introduce photosensitive groups into the molecular chain of organosiloxane to make it a photocurable polysiloxane. The general formula of silane coupling agent can be expressed as: R-SiX3. The photosensitizing group needs to be introduced through the R group or the X group. There is a risk of gelation during the preparation process, and the performance of the product is poor, which greatly limits the application and development of photosensitive silicone materials. Therefore, it is urgent to develop new photosensitive silicone materials with excellent performance. Summary of the invention

[0004] According to the first aspect of the present invention, there is provided a TPA-GMA-KH560 graft, the structural formula of which is:

[0005] Among them, R is

[0006] According to a second aspect of the present invention, a method for preparing the above-mentioned TPA-GMA-KH560 graft is provided, comprising the following steps:

[0007] Turpentine oil-based carboxylic acid (TPA), glycidyl methacrylate (GMA), a first catalyst, an inhibitor, and a first solvent are mixed, stirred at 70-80°C for 0.5-2h, then the temperature is adjusted to 75-95°C and the reaction is continued for 2-5h, and then the temperature is adjusted to 70-80°C, the first catalyst and γ-glycidyloxypropyltrimethoxysilane (KH560) are added, and the reaction is carried out at 70-90°C for 4-6h. After the reaction is completed, the first solvent is removed to obtain a TPA-GMA-KH560 graft (abbreviated as TGK).

[0008] The synthetic route of TGK of the present invention is as follows Figure 1 shown.

[0009] The turpentine-based carboxylic acid (TPA) of the present invention can be prepared according to the preparation method of the intermediate product polycarboxylic acid disclosed in the patent application with publication number CN 116478623 A.

[0010] In some embodiments, the first catalyst is at least one of tetrabutylammonium bromide, N'N-dimethylbenzylamine, triethylamine, N'N-dimethylethanolamine, and triphenylphosphine.

[0011] In some embodiments, the polymerization inhibitor is at least one of hydroquinone, p-hydroxyanisole, and 2,6-di-tert-butyl-p-cresol.

[0012] In some embodiments, the first solvent is at least one of acetone, butanone, toluene, xylene, and dichloromethane.

[0013] In some embodiments, the molar ratio of turpentine carboxylic acid, glycidyl methacrylate, and γ-glycidyloxypropyltrimethoxysilane is 1:(1-5):(1-5).

[0014] In some embodiments, the first catalyst is used in an amount of 0.1 to 1.5 wt % of the total amount of the reactants. When the first catalyst is added together with turpentine-based carboxylic acid and glycidyl methacrylate, the reactants refer to turpentine-based carboxylic acid and glycidyl methacrylate; when the first catalyst is added together with γ-glycidyloxypropyltrimethoxysilane, the reactants refer to turpentine-based carboxylic acid, glycidyl methacrylate and γ-glycidyloxypropyltrimethoxysilane.

[0015] In some embodiments, the amount of the polymerization inhibitor is 0.1-1 wt % of the total weight of the reactants. The reactants mentioned here refer to turpentine oil-based carboxylic acid and glycidyl methacrylate.

[0016] In some embodiments, the first solvent is used in an amount of 45-55 wt % of the sum of the mass of turpentine carboxylic acid and glycidyl methacrylate.

[0017] According to a third aspect of the present invention, there is provided a silicon-containing turpentine-based UV-curable acrylate prepolymer, which is obtained by hydrolyzing the above-mentioned TPA-GMA-KH560 graft.

[0018] According to a fourth aspect of the present invention, there is provided a method for preparing the above-mentioned silicon-containing turpentine-based UV-curable acrylate prepolymer, comprising the following steps:

[0019] The TPA-GMA-KH560 graft (TGK), the second catalyst, water and the second solvent are mixed evenly, and stirred at 50-90° C. for 3-10 hours to obtain a silicon-containing turpentine-based UV-curable acrylate prepolymer (abbreviated as TGK-OH).

[0020] The synthetic route of TGK-OH of the present invention is as follows Figure 2 As shown in the figure, the wavy lines in the TGK-OH structural formula can represent all the group structures shown in the structure, such as -OH, -H, -O-Si-, because TGK-OH is a polymer.

[0021] In some embodiments, the second catalyst is at least one of acrylic acid, hydrochloric acid, dibutyltin dilaurate, and sodium hydroxide.

[0022] In some embodiments, the second solvent is at least one of methanol, ethanol, propanol, butanol, ethylene glycol, ethylene oxide, triethanolamine, and xylene.

[0023] In some embodiments, the mass ratio of TPA-GMA-KH560 graft, water and the second solvent is 1:(0.2-1):(0.2-1), and the amount of the second catalyst is 2-10 wt % of the mass of the TPA-GMA-KH560 graft.

[0024] According to a fifth aspect of the present invention, there is provided a use of the above-mentioned silicon-containing turpentine-based UV-curable acrylate prepolymer in the preparation of UV-curable coatings, UV-curable inks, UV-curable adhesives or 3D printing materials.

[0025] According to a sixth aspect of the present invention, a UV curing film is provided, wherein the raw materials thereof comprise: 65-97 wt % of the above-mentioned silicon-containing turpentine-based UV curing acrylate prepolymer, 0-30 wt % of a reactive diluent, and 3-5 wt % of a photoinitiator.

[0026] In some embodiments, the reactive diluent is at least one of diethylene glycol diacrylate, triethylene glycol diacrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, tripropylene glycol diacrylate, and dipropylene glycol diacrylate.

[0027] In some embodiments, the photoinitiator is at least one of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone, (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, ethyl 2,4,6-trimethylbenzoylphenylphosphonate, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, bis-2,6-difluoro-3-pyrrolphenyl titanocene, and benzoin dimethyl ether.

[0028] The beneficial effects of the present invention include:

[0029] (1) The present invention uses glycidyl methacrylate (GMA) and γ-glycidyloxypropyl trimethoxysilane (KH560) to graft turpentine oil-based carboxylic acid (TPA), and uses the ring-opening reaction between carboxylic acid and epoxy group to introduce double bond groups containing UV curable and hydrolyzable alkoxy groups to obtain TPA-GMA-KH560 graft (TGK); then the TPA-GMA-KH560 graft is hydrolyzed by sol-gel method to obtain silicon-containing turpentine oil-based UV curable acrylate prepolymer (TGK-OH). On the one hand, the present invention uses turpentine oil-based carboxylic acid, a derivative of turpentine oil, as raw material, and introduces turpentine oil-based raw materials that do not occupy crop space into the preparation of UV-curable polymer materials, which can reduce the consumption of fossil energy; on the other hand, the present invention introduces silicone into UV curable materials, which can increase the chemical resistance of the materials. The Si-O-Si bond generated after the hydrolysis of TGK can also give the molecular chain a certain flexibility, so that the silicone polymer has good mechanical properties and thermal stability.

[0030] (2) The present invention combines silicone with UV curing technology. On the one hand, moisture-curable alkoxysilyl groups are introduced into the material, and the material has the effect of UV + moisture dual curing, which can reduce the stickiness of the material caused by incomplete UV curing. On the other hand, the Si-O-Si bonds generated by the ethoxy groups contained in KH560 after hydrolysis and the double bond structure in the introduced glycidyl methacrylate (GMA) molecules form a cross-linked interpenetrating network structure, which can greatly increase the cross-linking density of the material, thereby improving the comprehensive performance of the material. At the same time, the main chain structure of the silicone resin contains a high-density Si-O-Si structure, and the Si-O-Si bonds have a large bond angle. The Si-O-Si main chain structure can give the silicone molecular chain a certain flexibility, thereby making the silicone polymer have good mechanical properties, thermal stability and chemical resistance.

[0031] (3) The present invention utilizes a sol-gel method to hydrolyze the TPA-GMA-KH560 graft to obtain a silicon-containing polymer. The hydrolysis only needs to be carried out at a temperature slightly higher than room temperature and under normal pressure, and the reaction conditions are mild. The proportions of various components are easy to control, and the prepared cured film has good dispersion properties. The present invention forms an inorganic skeleton at a relatively low temperature, is easy to shape and dope, and can introduce an inorganic phase into the organic phase without reducing the performance of the cured film.

[0032] (4) The present invention prepares a UV-cured film by mixing a silicon-containing turpentine-based UV-cured acrylate prepolymer with a reactive diluent and a photoinitiator. The prepared UV-cured film exhibits excellent dynamic mechanical properties and crosslinking density, thermal stability and a higher gel fraction. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The synthetic route of the TPA-GMA-KH560 graft (TGK) of the present invention.

[0034] Figure 2 The synthetic route of the silicon-containing turpentine-based UV-curable acrylate prepolymer (TGK-OH) of the present invention is shown.

[0035] Figure 3 These are the infrared spectrum detection results of the TPA-GMA graft (TG), TPA-GMA-KH560 graft (TGK), and silicone-containing turpentine-based UV-curable acrylate prepolymer (TGK-OH) of Example 1 of the present invention.

[0036] Figure 4 This is the hydrogen nuclear magnetic resonance spectrum of the raw material γ-glycidyloxypropyltrimethoxysilane (KH560) and the intermediate product TPA-GMA-KH560 graft (TGK) of Example 1 of the present invention.

[0037] Figure 5 The dynamic thermodynamics (DMA) test results of the UV-cured films S1-S4 of the present invention are shown in FIG.

[0038] Figure 6 The thermal stability test results of the UV-cured films S1-S4 of the present invention are shown in FIG.

[0039] Figure 7 The gel fraction test results of the UV-cured films S1-S4 of the present invention are shown in FIG. DETAILED DESCRIPTION

[0040] The present invention is further described in detail below in conjunction with specific examples, but the embodiments of the present invention are not limited thereto. The raw materials involved in the following examples can all be obtained from commercial channels.

[0041] In the following examples, the turpentine oil-based carboxylic acid (TPA) used was prepared by the following method:

[0042] 100g of turpentine and 61.78g of maleic anhydride were added to a three-necked flask, reacted at 160°C for 18h, and the remaining turpentine was removed to obtain turpentine-based anhydride. 100g of the prepared turpentine-based anhydride was taken, an equal amount of anhydrous ethanol (analytical grade) was added, and reacted at 80°C for 1h, and then a 10wt% sodium hydroxide-ethanol solution was added (10g of sodium hydroxide solid was weighed, mixed with 90g of anhydrous ethanol (analytical grade), and then a glass rod was used to stir to completely dissolve the sodium hydroxide solid to obtain a sodium hydroxide-ethanol solution), the pH value of the reaction solution was about 9.5, the reaction solution was allowed to stand for about 5h, and then a 10% hydrogen chloride-water solution was added to reduce the pH value of the reaction solution to about 3.5, and after removing excess water, turpentine-based carboxylic acid was obtained.

[0043] The relative molecular mass of the obtained turpentine oil-based carboxylic acid (TPA) is about 1080 g / mol.

[0044] Example 1

[0045] The method for preparing the silicon-containing turpentine-based UV-curable acrylate prepolymer of this embodiment comprises the following steps:

[0046] (1) 10.00 g of turpentine carboxylic acid (TPA), 5.29 g of glycidyl methacrylate (GMA), 0.08 g of the first catalyst triethylamine and 0.04 g of the inhibitor hydroquinone were added to a reaction container, and 7.65 g of the first solvent acetone was added to reduce the viscosity of the system. After stirring at 70° C. for 30 min, the temperature was raised to 75° C. and the reaction was continued for 2 h to obtain a TPA-GMA graft (abbreviated as TG); then, the reaction temperature was kept constant at 75° C., and a mixed solution of 0.10 g of the first catalyst triethylamine and 4.40 g of γ-glycidyloxypropyltrimethoxysilane (KH560) was added to the system using a constant pressure dropping funnel, and the mixture was reacted at 75° C. for 4 h. After the solvent was removed by a rotary evaporator, the product TPA-GMA-KH560 graft (abbreviated as TGK) was obtained;

[0047] The molar ratio of TPA to GMA and KH560 is 1:4:2, the amount of the first catalyst is 0.5wt% of the total amount of reactants, and the amount of the inhibitor hydroquinone is 0.2wt% of the total mass of reactants.

[0048] (2) 19.69 g of the product TGK obtained in step (1), 1.97 g of the second catalyst acrylic acid, 9.85 g of distilled water and 9.85 g of the second solvent ethanol were added to a 500 mL round-bottom flask, mixed evenly, and then stirred at 60° C. for 5 h to obtain a silicon-containing turpentine-based UV-curable acrylate prepolymer (abbreviated as TGK-OH);

[0049] The mass ratio of TGK, distilled water and the second solvent ethanol is 1:0.5:0.5, and the amount of the second catalyst acrylic acid is 10 wt % of the total amount of reactants.

[0050] Example 2

[0051] The method for preparing the silicon-containing turpentine-based UV-curable acrylate prepolymer of this embodiment comprises the following steps:

[0052] (1) 10.00 g of turpentine carboxylic acid (TPA), 3.97 g of glycidyl methacrylate (GMA), 0.07 g of the first catalyst tetrabutylammonium bromide and 0.04 g of the inhibitor hydroquinone were added to a reaction container, and 6.99 g of the first solvent butanone was added to reduce the viscosity of the system. After stirring at 80° C. for 30 min, the temperature was raised to 95° C. and the reaction was continued for 3 h to obtain a TPA-GMA graft (abbreviated as TG); then the temperature was lowered to 80° C., and a mixed solution of 0.10 g of the first catalyst triethylamine and 6.59 g of γ-glycidyloxypropyltrimethoxysilane (KH560) was added to the system using a constant pressure dropping funnel, and the mixture was reacted at 80° C. for 5 h. After removing the solvent using a rotary evaporator, the product TPA-GMA-KH560 graft (abbreviated as TGK) was obtained;

[0053] The molar ratio of TPA to GMA and KH560 is 1:3:3, the amount of the first catalyst is 0.5wt% of the total amount of reactants, and the amount of the inhibitor is 0.3wt% of the total mass of reactants.

[0054] (2) 20.56 g of the product TGK obtained in step (1), 0.41 g of the second catalyst hydrochloric acid (analytical grade), 10.28 g of distilled water and 10.28 g of the second solvent methanol were added to a 500 mL round-bottom flask, mixed evenly, and then stirred at 70° C. for 5 h to obtain a silicon-containing turpentine-based UV-curable acrylate prepolymer (abbreviated as TGK-OH);

[0055] The mass ratio of TGK, distilled water and the second solvent is 1:0.5:0.5, and the amount of the second catalyst is 2 wt % of the total amount of reactants.

[0056] Example 3

[0057] The method for preparing the silicon-containing turpentine-based UV-curable acrylate prepolymer of this embodiment comprises the following steps:

[0058] (1) 17.17 g of turpentine carboxylic acid (TPA), 6.78 g of glycidyl methacrylate (GMA), 0.19 g of the first catalyst tetrabutylammonium bromide and 0.12 g of the inhibitor p-hydroxyanisole were added to a reaction container, and 11.98 g of the first solvent acetone was added to reduce the viscosity of the system. After stirring at 70° C. for 30 min, the temperature was raised to 90° C. and the reaction was continued for 3.5 h to obtain a TPA-GMA graft (abbreviated as TG); then the temperature was lowered to 75° C., and a mixed solution of 0.28 g of the first catalyst tetrabutylammonium bromide and 11.27 g of γ-glycidyloxypropyltrimethoxysilane (KH560) was added dropwise to the system using a constant pressure dropping funnel, and the mixture was reacted at 75° C. for 4.5 h. After removing the solvent using a rotary evaporator, a product TPA-GMA-KH560 graft (abbreviated as TGK) was obtained;

[0059] The molar ratio of TPA to GMA and KH560 is 1:3:3, the amount of the first catalyst is 0.8wt% of the total amount of reactants, and the amount of the inhibitor is 0.50wt% of the total mass of reactants.

[0060] (2) 35.05 g of the product TGK obtained in step (1), 1.05 g of the second catalyst dibutyltin dilaurate, 21.03 g of distilled water and 14.02 g of the second solvent methanol were added to a 500 mL round-bottom flask, mixed evenly, and then stirred at 85° C. for 3.5 h to obtain a silicon-containing turpentine-based UV-curable acrylate prepolymer (abbreviated as TGK-OH);

[0061] The mass ratio of TGK, distilled water and the second solvent is 1:0.6:0.4, and the amount of the second catalyst is 3 wt % of the total amount of reactants.

[0062] Example 4

[0063] The method for preparing the silicon-containing turpentine-based UV-curable acrylate prepolymer of this embodiment comprises the following steps:

[0064] (1) 10.00 g of turpentine carboxylic acid (TPA), 1.32 g of glycidyl methacrylate (GMA), 0.11 g of the first catalyst triphenylphosphine and 0.08 g of the inhibitor 2,6-di-tert-butyl-p-cresol were added to a reaction container, and 5.66 g of the first solvent acetone was added to reduce the viscosity of the system. After stirring at 80° C. for 30 min, the temperature was raised to 90° C. and the reaction was continued for 5 h to obtain a TPA-GMA graft (abbreviated as TG); then the temperature was lowered to 75° C., and a mixed solution of 0.22 g of the first catalyst tetrabutylammonium bromide and 10.99 g of γ-glycidyloxypropyltrimethoxysilane (KH560) was added dropwise to the system using a constant pressure dropping funnel, and the mixture was reacted at 85° C. for 4.5 h. After the solvent was removed by a rotary evaporator, the product TPA-GMA-KH560 graft (abbreviated as TGK) was obtained;

[0065] The molar ratio of TPA to GMA and KH560 is 1:1:5, the amount of the first catalyst is 1.00wt% of the total amount of reactants, and the amount of the inhibitor is 0.7wt% of the total mass of reactants.

[0066] (2) 23.63 g of the product TGK obtained in step (1), 1.89 g of the second catalyst acrylic acid, 7.09 g of distilled water and 16.54 g of the second solvent propanol were added to a 500 mL round-bottom flask, mixed evenly, and then stirred at 85° C. for 3.5 h to obtain a silicon-containing turpentine-based UV-curable acrylate prepolymer (abbreviated as TGK-OH);

[0067] The mass ratio of TGK, distilled water and the second solvent is 1:0.3:0.7, and the amount of the second catalyst is 8wt% of the total amount of reactants.

[0068] Next, the performance tests were conducted on the intermediate products obtained in Examples 1-4 and the silicon-containing turpentine-based UV-curable acrylate prepolymers:

[0069] 1. The TPA-GMA graft (TG), TPA-GMA-KH560 graft (TGK), and silicon-containing turpentine-based UV-curable acrylate prepolymer (TGK-OH) of Example 1 were tested by infrared spectroscopy. The results are shown in Figure 3 .

[0070] exist Figure 3 In the infrared curve of TG, 3470 cm -1 The characteristic absorption peak of hydroxyl group appears at 3200-2500cm, which is generated by the ring-opening reaction of turpentine carboxylic acid (TPA) and glycidyl methacrylate (GMA) epoxy group. -1 There are also broad and scattered peaks caused by the remaining carboxylic acids, 1635cm -1 The characteristic absorption peak of double bond appears at 910cm-1 The characteristic absorption peak of epoxy in GMA is not observed at 2840 cm-1, indicating that GMA successfully reacts with TPA and the reaction is complete. -1 The vibration absorption peak of Si-O-CH3 newly generated at 816cm -1 The absorption peak at 910 cm-1 is obviously broadened and deepened due to the introduction of Si-OC bond from KH560. -1 The characteristic absorption peak of the epoxy group of KH560 also basically disappeared, proving that KH560 and carboxylic acid also successfully underwent an epoxy-opening reaction. -1 The characteristic peak of hydroxyl groups near the surface becomes darker, 2840 cm -1 The characteristic absorption peak of Si-O-CH3 disappeared, and the peak at 1167cm -1 、1104cm -1 The absorption peak broadened and deepened, indicating that Si-O-CH3 was hydrolyzed to generate silanol Si-OH, and partially condensed to form Si-O-Si bonds, which overlapped with -COOC- in TGK.

[0071] 2. The raw material γ-glycidyloxypropyltrimethoxysilane (KH560) and the intermediate product TPA-GMA-KH560 graft (TGK) of Example 1 were characterized by nuclear magnetic resonance. The results are shown in Figure 4 .

[0072] Depend on Figure 4 From the H NMR spectra of KH560 and TGK, we can see that the chemical shift at 2.58-2.71ppm corresponds to the absorption of proton hydrogen on the epoxy group at positions 1 and 2 in KH560, while in the TGK curve, the chemical shift at this position is significantly reduced, proving that the epoxy group has a ring-opening reaction with the carboxylic acid in TPA, but there is a surplus of epoxy. At 3.90ppm, a chemical shift of methylene hydrogen connected to the hydroxyl group, i.e., positions 10 and 13, further proves that the epoxy and carboxylic acid open the ring oxygen, the chemical shift at 5.69-6.06ppm belongs to the absorption of double bond proton hydrogen brought by GMA, and the chemical shift at 3.96-4.11ppm comes from the chemical shift of chemical hydrogen at positions 9, 11, 12, and 14.

[0073] 3. Preparation and performance testing of UV curing film

[0074] Application Example 1

[0075] An appropriate amount of the silicon-containing turpentine-based UV-curable acrylate prepolymer (TGK-OH) prepared in Example 1 was weighed and placed in a beaker, 5 wt % of a photoinitiator (2,4,6-trimethylbenzoyl) diphenylphosphine oxide and 30 wt % of a reactive diluent diethylene glycol diacrylate were added, and stirred evenly to obtain a mixture. The obtained mixture was then poured into a silica gel plate sample strip preparation device and irradiated under ultraviolet light with a wavelength of 200 nm-450 nm for 10 min to obtain a UV-cured film, which was named S1.

[0076] Application Example 2

[0077] An appropriate amount of the silicon-containing turpentine-based UV-curable acrylate prepolymer (TGK-OH) prepared in Example 2 was weighed and placed in a beaker, and 5 wt % of a photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone and 20 wt % of a reactive diluent diethylene glycol diacrylate were added and stirred evenly to obtain a mixture. The obtained mixture was then poured into a silica gel plate sample strip preparation device for ultraviolet irradiation to obtain a UV-cured film, which was named S2.

[0078] Application Example 3

[0079] An appropriate amount of the silicon-containing turpentine-based UV-curable acrylate prepolymer (TGK-OH) prepared in Example 3 was weighed and placed in a beaker, and 5 wt % of a photoinitiator 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone and 10 wt % of a reactive diluent tripropylene glycol diacrylate were added, and stirred evenly to obtain a mixture. The obtained mixture was then poured into a silica gel plate sample strip preparation device for ultraviolet irradiation to obtain a UV-cured film, which was named S3.

[0080] Application Example 4

[0081] An appropriate amount of the silicon-containing turpentine-based UV-curable acrylate prepolymer (TGK-OH) prepared in Example 4 was weighed and placed in a beaker, and 5 wt % of a photoinitiator 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester was added and stirred evenly to obtain a mixture. The obtained mixture was then poured into a silica gel plate sample strip preparation device for ultraviolet irradiation to obtain a UV-cured film, which was named S4.

[0082] Then, the prepared UV curing films S1-S4 were subjected to the following performance tests:

[0083] (1) Dynamic thermodynamic (DMA) test

[0084] The UV-cured film was tested by a dynamic thermomechanical analyzer. Figure 5 and Table 1. The crosslinking density of the UV-cured film can be calculated by the formula E'=3RT'×V eCalculation is performed, where T' is the absolute temperature of the cross-linked film in the rubber state (T g +30°C), E' is the storage modulus at T', and R represents the gas constant.

[0085] Table 1 Dynamic mechanical properties and crosslinking density of UV-cured films

[0086] sample <![CDATA[T g (℃)]]> <![CDATA[E’ 25 (MPa)]]> <![CDATA[E’ atTg+30 (MPa)]]> <![CDATA[V e (×10 3 mol·m -3 )]]> S1 66.10 715.48 24.95 2.71 S2 65.70 847.46 29.07 3.16 S3 55.60 894.39 30.91 3.45 S4 54.60 961.77 39.22 4.40

[0087] It can be seen from Table 1 that the crosslinking density of the sample increases with the increase of the content of the silicon-containing prepolymer (TGK-OH) in the system. This may be because as the content of the active diluent gradually decreases, more silicon-containing prepolymers in the system form more Si-O-Si bonds through hydrolysis and condensation, and form a crosslinked interpenetrating network structure with the carbon-carbon double bonds contained in the prepolymer itself, thereby increasing the crosslinking density of the cured film.

[0088] Depend on Figure 5 It can be seen that each curve has only one peak, indicating that the components of the cured film have good compatibility. The peak value corresponding to Tanδ is the glass transition temperature of the cured film at this temperature. The prepared cured films S1-S4 all have high glass transition temperatures. This is because turpentine oil-based carboxylic acid contains a six-membered ring structure and has a certain rigidity. The introduction of turpentine oil-based carboxylic acid into the material can increase the glass transition temperature of the material. From S1 to S4, as the content of the active diluent decreases, the glass transition temperature of the sample decreases. This may be because as the content of the active diluent decreases, the content of the silicon-containing prepolymer (TGK-OH) in the system increases, and the presence of silicon in TGK-OH plays a certain role in the flexible segment, thereby reducing the glass transition temperature of the cured film.

[0089] (2) Thermal stability test

[0090] The samples were subjected to thermogravimetric testing using a German NETZSCH TG 209F1 Libra analyzer. -1 In a nitrogen atmosphere, the temperature range is 30~800℃, and the heating rate is 10℃·min -1 The test results are shown in Figure 6 and Table 2. Figure 6 The TGA curves (a) and DTG curves (b) of UV-cured films with different active diluent contents are shown in Table 2. The degradation temperatures (T 5% ), degradation temperature when degradation is 50% (T 50% ), maximum thermal degradation temperature (T max ) and residual carbon rate (W char ), where the residual carbon rate of the sample is measured at 800°C.

[0091] Table 2 Thermal degradation values ​​of UV-cured films

[0092] sample <![CDATA[T 5% (℃)]]> <![CDATA[T 50% (℃)]]> <![CDATA[T max (℃)]]> Carbon residue rate (%) S1 175.08 396.08 388.6 13.40 S2 183.37 398.87 403.1 16.26 S3 211.42 400.92 403.6 16.88 S4 253.14 406.64 410.7 17.76

[0093] from Figure 6 It can be seen that the prepared UV-curable film is mainly divided into two degradation stages. The degradation temperature of the first degradation stage is mainly between 50℃ and 300℃, and this stage is mainly the decomposition of residual moisture, catalysts, solvents and raw materials in the cured film. The thermal degradation temperature of the second stage is mainly between 350℃ and 420℃, and this stage is mainly the decomposition of silicon-containing compounds and molecular chains, as well as the carbonization of cross-linked polymers.

[0094] As shown in Table 2, with the decrease of the amount of active diluent added, the thermal degradation temperature of each stage of the cured film increases. This is because the active diluent has a lower double bond density. With the decrease of the amount of active diluent added, the content of TGK-OH prepolymer in the system will increase relatively. After hydrolysis, TGK-OH is a high molecular polymer with a main chain structure of repeated Si-O bonds and a turpentine-based UV curing group connected to the Si atom. The bond energy of the Si-O bond is as high as 1014.12KJ / mol, which is much larger than the bond energy of the CC bond and the CO bond. This makes the UV-cured film containing silicone have good high and low temperature resistance. On the other hand, after the hydrolysis and condensation of the TGK-OH prepolymer, the generated Si-O-Si bond and the carbon-carbon double bond form a cross-linked interpenetrating network structure, which greatly improves the cross-linking density of the cured film, thereby increasing the thermal stability of the cured film. In addition, as the content of active diluent in the system decreases, the residual carbon rate of the cured film also increases accordingly, from 13.40% of the S1 sample to 17.76% of the S4 (blank) sample. This is because the Si element contained in the material can form high-temperature resistant silica at high temperatures and promote the formation of more carbon layers, thereby reducing the rate of mass loss of the cured film sample and improving the high-temperature resistance of the cured film.

[0095] (3) Gel rate test

[0096] The gel fraction can be used as an indicator to evaluate the crosslinking density of the cured film. The gel fractions of the cured film samples with different amounts of active diluent added are as follows: Figure 7 shown.

[0097] Depend on Figure 7It can be seen that the prepared cured film samples all have a high gel fraction (above 92%). As the content of the active diluent decreases, the gel fraction of the sample gradually increases, from 92.78% of the S1 sample to 95.29% of the S4 sample, indicating that after the amount of active diluent added is reduced, the crosslinking density of the cured film is increased. This is because after the content of the active diluent is reduced, the content of the prepolymer in the system is relatively increased, and the double bond density and the Si-O-Si bond content will also increase relatively. The double bonds and the Si-O-Si bonds formed by hydrolysis condensation can form a crosslinked interpenetrating network structure, which increases the crosslinking density of the entire system, thereby making the cured film show a higher gel fraction.

[0098] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a TPA-GMA-KH560 grafted product, characterized in that: The steps include: Mix turpentine oil-based carboxylic acid, glycidyl methacrylate, the first catalyst, the polymerization inhibitor, and the first solvent, stir at 70-80°C for 0.5-2h, then adjust the temperature to 75-95°C and continue to react for 2-5h, then adjust the temperature to 70-80°C, add the first catalyst and γ-glycidyloxypropyltrimethoxysilane, react at 70-90°C for 4-6h, remove the first solvent after the reaction is completed, and obtain; The molar ratio of the turpentine oil-based carboxylic acid, glycidyl methacrylate and γ-glycidyloxypropyltrimethoxysilane is 1:(1-5):(1-5).

2. The method for preparing the TPA-GMA-KH560 graft according to claim 1, characterized in that: The first catalyst is at least one of tetrabutylammonium bromide, N'N-dimethylbenzylamine, triethylamine, N'N-dimethylethanolamine, and triphenylphosphine; The polymerization inhibitor is at least one of hydroquinone, p-hydroxyanisole, and 2,6-di-tert-butyl-p-cresol; The first solvent is at least one of acetone, butanone, toluene, xylene and dichloromethane.

3. The method for preparing the TPA-GMA-KH560 graft according to claim 1 or 2, characterized in that: The first catalyst is used in an amount of 0.1 to 1.5 wt% of the total amount of reactants; The amount of the polymerization inhibitor is 0.1 to 1 wt% of the total mass of the reactants; The amount of the first solvent used is 45-55 wt % of the sum of the mass of turpentine oil-based carboxylic acid and glycidyl methacrylate.

4. TPA-GMA-KH560 grafted product obtained by the preparation method according to any one of claims 1 to 3.

5. Silicone-containing turpentine-based UV-curable acrylate prepolymer, characterized in that: It is obtained by hydrolyzing the TPA-GMA-KH560 grafted product described in claim 4.

6. The method for preparing the silicon-containing turpentine-based UV-curable acrylate prepolymer according to claim 5, characterized in that: The steps include: The TPA-GMA-KH560 grafted product, the second catalyst, water and the second solvent are mixed evenly, and stirred at 50-90° C. for 3-10 hours to obtain the product.

7. The method for preparing a silicon-containing turpentine-based UV-curable acrylate prepolymer according to claim 6, characterized in that: The second catalyst is at least one of acrylic acid, hydrochloric acid, dibutyltin dilaurate, and sodium hydroxide; The second solvent is at least one of methanol, ethanol, propanol, butanol, ethylene glycol, ethylene oxide, triethanolamine, and xylene.

8. The method for preparing a silicon-containing turpentine-based UV-curable acrylate prepolymer according to claim 6 or 7, characterized in that: The mass ratio of the TPA-GMA-KH560 graft, water and the second solvent is 1:(0.2-1):(0.2-1), and the amount of the second catalyst is 2-10wt% of the mass of the TPA-GMA-KH560 graft.

9. Use of the silicon-containing turpentine-based UV-curable acrylate prepolymer according to claim 5 in the preparation of UV-curable coatings, UV-curable inks, and UV-curable adhesives.

10. A UV curable film, characterized in that: The raw material composition comprises: 65-97wt% of the silicon-containing turpentine-based UV-curable acrylate prepolymer described in claim 5, 0-30wt% of an active diluent, and 3-5wt% of a photoinitiator.

Citation Information

Patent Citations

  • Turpentine-based UV-cured acrylate prepolymer as well as preparation method and application thereof

    CN116478623A

  • Preparation method of turpentine-based acrylate modified waterborne polyurethane emulsion

    CN103172796A

  • Financial credit card binder

    CN105713526A